Creatine supplementation increases total body water in soccer players: a deuterium oxide dilution study - Deminice, R.; Rosa, F. T.; Pfrimer, K.; Ferrioli, E.; Jordao, A. A.; Freitas, E. (International Journal of Sports Medicine, 2016)
This study aimed to evaluate changes in total body water (TBW) in soccer athletes using a deuterium oxide dilution method and bioelectrical impedance (BIA) formulas after 7 days of creatine supplementation. In a double-blind controlled manner, 13 healthy (under-20) soccer players were divided randomly in 2 supplementation groups: Placebo (Pla, n=6) and creatine supplementation (CR, n=7). Before and after the supplementation period (0.3 g/kg/d during 7 days), TBW was determined by deuterium oxide dilution and BIA methods. 7 days of creatine supplementation lead to a large increase in TBW (2.3±1.0?L) determined by deuterium oxide dilution, and a small but significant increase in total body weight (1.0±0.4 kg) in Cr group compared to Pla. The Pla group did not experience any significant changes in TBW or body weight. Although 5 of 6 BIA equations were sensitive to determine TBW changes induced by creatine supplementation, the Kushner et al. [16] method presented the best concordance levels when compared to deuterium dilution method. In conclusion, 7-days of creatine supplementation increased TBW determined by deuterium oxide dilution or BIA formulas. BIA can be useful to determine TBW changes promoted by creatine supplementation in soccer athletes, with special concern for formula choice.